Feeding patterns of sitatunga (Tragelaphus Speki) in the Rushebeya-Kanyabaha wetland, south western Uganda - Tweheyo, Mnason; Kacebonaho Amanya, Bruce; Turyahabwe, Nelson (African Journal of Ecology, 2010)
Feeding patterns and habits of sitatunga were assessed in Rushebeya-Kanyabaha wetland between June 2006 and July 2007. Sixty transects were cut at intervals of 250 m along which sitatunga dung piles, habitats used and diet were identified from feeding signs or plant damage. Household interviews were also conducted in villages adjacent to the wetland to understand plants and crops known to be fed on by sitatunga, type of damage, frequency of sitatunga farm visits and their methods to control crop raiding. Sitatunga mostly fed on leaves (60%) and in the wetland edge (WE) habitat (49%). Forty plant species were recorded to be eaten with herbs as majority (33%) and of crops sweet potatoes were most raided. Sitatungas are basically solitary species with 73% of the sightings being of a single individual. They had mornings and late evenings as their movement peaks and preferred to feed on broad leaved plants. There were significant relationships between both habitat use and food preferences with seasons. We predict that because of seasonal food variations, crop raiding would increase and may result into more negative attitudes by farmers to sitatunga. More research on farmers’ sensitization, population census, behaviours and ecotourism are necessary for this species conservation.
Keywords: Feeding patterns; Tragelaphus speki; Wetlands